Early Spondyloarthritis Clinic: Organizational Improvements in the Patient Journey - D'Angelo, Salvatore; Afeltra, Antonella; Atzeni, Fabiola; Baldissera, Elena; Caminiti, Maurizio; Ciccia, Francesco; D'Agostino, Maria Antonietta; Dagna, Lorenzo; Erre, Gian Luca; Franceschini, Franco; Fusaro, Enrico; Giacomelli, Roberto; et al. (Frontiers in Medicine, 2022)
Spondyloarthritis are chronic inflammatory diseases affecting spine, peripheral joints and enthesis, as well as extra-articular sites (bowel, eyes, skin). Diagnosis of spondyloarthritis often is slow and requires a multidisciplinary approach. The “Early SpA Clinic” project aimed at improving the patient care and journeys, by solving some organizational issues existing in Rheumatology Clinics. The “Early SpA Clinic” involved 19 Italian Rheumatology Centers using in-depth organizational analyses to identify areas for improvement. From the results of the analyses, some organizational solutions were suggested, and their impact measured at the end of the project through specific KPI. With the implementation of the suggested organizational solutions, Centers achieved relevant results, positively impacting on all the phases of the patient journey: decrease in waiting lists (−23%) and in the time length to transit the Center (−22%), increase in the percentage of new diagnoses (+20%), in the saturation of outpatient clinic capacity (+16%), and in the patient satisfaction (+4%). Centers involved in the “Early SpA Clinic” implemented several organizational actions based on an overall assessment of their activities and on solutions that required no additional resources. Overall, the Centers achieved the “Early SpA Clinic” objectives in terms of better management of resources, personnel, spaces, equipment, in relation to the volumes of patients.